Targets and Fisheries Management in the Asia and Pacific Region. Issue 3 (17th September 2014) - Chu, Long; Kompas, Tom
Abstract Marine fisheries in the Asia and the Pacific region play an important role in global, regional and national economies. Many of the fisheries in the region are over‐exploited, both biologically and economically. We focus on the use of appropriate fishery targets, and the importance of tying those targets to management objectives to overcome the usual and unwanted negative externalities that occur in ocean fisheries, the ones that result in substantial over‐fishing. Of particular importance is the use of a maximum economic yield target for both short‐ and long‐lived species. Maximum economic yield, when combined with appropriately designed marine protected areas, or marine reserves, not only provides maximum profitability and generally larger and more 'conservationist' stocks of fish, but it also ensures a measure of resilience from stochastic shocks that may negatively impact the fishery. It remains the preferred target for most fisheries in the Asia and Pacific region.